1976
DOI: 10.1136/bmj.1.6018.1116
|View full text |Cite
|
Sign up to set email alerts
|

A controlled comparison of flupenthixol and amitriptyline in depressed outpatients.

Abstract: high-frequency stimulator that blankets the re-entry zone, and thereby fortuitously induces a suitably timed extrasystole ;3 and the variable-hysteresis orthorhythmic pacemaker.2 These are all experimental, and implantable units are not available. Fixedrate pacing, however, is known to be of value in some cases, and this may be achieved either by using a demand pacemaker with a magnetic reed switch activated by an external magnet' or by holding an external induction-coil5 or radio-frequency pacemaker6 over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Future studies might test alternative treatment strategies for patients with depression complicated by persistent insomnia. Although tricyclic antidepressants (TCAs) have been largely replaced by newer drug classes because of their autonomic and cardiovascular side effects, their ability to improve not only insomnia (Haskell et al 1975;Vaisanen et al 1978;Young et al 1976), but also sleep quality (Buysse et al 1996;Feuillade et al 1992;Hajak et al 2001;Roth et al 1982;Shipley et al 1985) is well established. "Second-generation" sedating antidepressants trazodone and nefazodone (Manber et al 2003;Thase et al 2002) also improve sleep quality and provide another antidepressant monotherapy option for these patients, although their benefits need to be weighed against possible cardiovascular side effects of trazodone and the risk of hepatic failure, which resulted in the boxed warning for nefazodone.…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…Future studies might test alternative treatment strategies for patients with depression complicated by persistent insomnia. Although tricyclic antidepressants (TCAs) have been largely replaced by newer drug classes because of their autonomic and cardiovascular side effects, their ability to improve not only insomnia (Haskell et al 1975;Vaisanen et al 1978;Young et al 1976), but also sleep quality (Buysse et al 1996;Feuillade et al 1992;Hajak et al 2001;Roth et al 1982;Shipley et al 1985) is well established. "Second-generation" sedating antidepressants trazodone and nefazodone (Manber et al 2003;Thase et al 2002) also improve sleep quality and provide another antidepressant monotherapy option for these patients, although their benefits need to be weighed against possible cardiovascular side effects of trazodone and the risk of hepatic failure, which resulted in the boxed warning for nefazodone.…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…In a two-arm non-placebocontrolled study, Young et al (1976) found that in mild to moderate depression, flupentixol had antidepressant efficacy comparable to that of amitriptyline, with greater anti-anxiety effects.…”
Section: Flupentixol (Flupenthixol) (Table 1)mentioning
confidence: 99%
“…The principal aim of this trial was to assess the role of the convulsion in the efficacy of ECT. A second example is the comparison of flupenthixol and amitriptyline in the treatment of mild or moderately severe depression not requiring ECT in 60 out-patients (Young et al 1976); the two treatments were prescribed using flexible dose schedules for a period of 6 weeks and assessed using observer-rated and self-rated scales at initial examination and after 1, 3 and 6 weeks of treatment. The aim of the study was a controlled comparison of flupenthixol against a standard tricyclic compound in depressed out-patients.…”
Section: Type Of Clinical Trialmentioning
confidence: 99%